Enhanced PIEZO1 function contributes to the pathogenesis of sickle cell disease - Luis O. Romero; Manisha Bade; Laila Elsherif; Jada D. Williams; Xiangmei Kong; Adebowale Adebiyi; Kenneth I. Ataga; Shang Ma; Julio F. Cordero-Morales; Valeria Vásquez (Proceedings of the National Academy of Sciences, 2025)
Sickle cell disease (SCD), an inherited blood disorder caused by a mutation in the β-globin gene, is characterized by sickle erythrocytes that are prone to hemolysis, leading to anemia and vaso-occlusion crises. In sickle erythrocytes, hemoglobin aggregation is followed by altered cation permeability and subsequent dehydration. Interventions that restore cation permeability can decrease hemolysis and ameliorate the symptoms associated with SCD. PIEZO1 is a nonselective mechanosensitive cation channel that regulates erythrocyte volume. Gain-of-function (GOF) mutations in PIEZO1 cause hemolytic anemia by increasing cation permeability, leading to erythrocyte dehydration in humans and mice. Although PIEZO1 plays a key role in erythrocyte homeostasis, its role in SCD remains unknown. Here, we demonstrate that the function of the PIEZO1 channel is upregulated in sickle erythrocytes of humans and mice, and this enhancement can be restored through a dietary intervention. We found that PIEZO1 activity in sickle erythrocytes resembles that of the GOF mutation causing hemolytic anemia. A diet enriched in the ω -3 fatty acid eicosapentaenoic (EPA) acid decreases PIEZO1 activity in sickle erythrocytes, attenuates hemolysis, and reduces hypoxia-induced sickling. Furthermore, EPA reduces inflammatory markers. We propose that PIEZO1 contributes to the increase in nonselective cationic conductance (i.e., Psickle), which leads to dehydration downstream of hemoglobin polymerization. Our results suggest that reducing PIEZO1 function represents a promising therapeutic strategy to reestablishing normal cation permeability in SCD.